Análise da relação entre a gestão estratégica de mudanças climáticas inserida no modelo de negócios circular, a reputação corporativa e as políticas públicas - Frizzo, Kamila (2023)
Climate change resulting from the externalities generated by the linearity of the production and consumption economic model causes various risks to society and organizations. However, the challenges associated with these changes may bring opportunities, driving actions and new businesses and contributing to sustainable development. Therefore, this study aimed to analyse the relationship between the strategic management of climate change within the circular business model, the reputation of industrial companies and public policies. The first phase of the research, characterized as qualitative, was carried out from a multiple case study with three Brazilian companies. The results of this phase allowed concluding that the investigated companies have strategic management of climate change, evidencing a relationship between the mitigation and adaptation practices and three other factors: transition to a circular business model, corporate reputation, and public policies. Thus, based on the results of the qualitative stage, it was possible to confirm the assumption that strategic management of climate change is associated with the circular business model, corporate reputation, and involvement in public policies in the Brazilian organizational context. The second stage of the study, characterized as quantitative, comprised a survey research with Brazilian industrial companies. The results of this second phase made it possible to observe that strategic management of climate change embedded in the circular business model is related to reputation and public policies, as positive associations were found between the dimensions of dependent and independent variables. It was also possible to notice distinctions between the adoption of climate change strategic management, the circular business model innovation degree, the corporate reputation degree, and the engagement public policies degree, given the significant distinctions found in the mean difference test.